1971
DOI: 10.1002/art.1780140505
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile ankylosing spondylitis

Abstract: Fifteen patients with juvenile ankylosing spondylitis were reviewed. Eight presented with extraspinal arthritis. Certain clinical features were of value early in the disease in distinguishing these patients from those with juvenile rheumatoid arthritis: male sex, remittent oligoarthritis, late onset in childhood, relative sparing of hands and wrists, infrequent cervical spine involvement, and negative tests for rheumatoid factors and antinuclear antibodies. Roentgenographic demonstration of sacroiliac arthriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
9
1
2

Year Published

1974
1974
2002
2002

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 33 publications
(11 reference statements)
6
9
1
2
Order By: Relevance
“…Hip disease, which in other studies (3,11,17,48) was shown to influence functional outcome in patients with juvenile-onset AS, became prominent in our group some years after onset. Although we confirmed the predominance of pauciarthritis as reported by others (3)(4)(5)(6)11,(13)(14)(15)(16)(17)(18)(19), its value as a discriminator between juvenile-onset AS and JRA was only marginal at 6 months. Furthermore, the number of patients with juvenile-onset AS extending to polyarthritis at the end of the first year of disease increased steadily thereafter.…”
Section: Burgos-vargas and Vazquez-melladosupporting
confidence: 83%
See 4 more Smart Citations
“…Hip disease, which in other studies (3,11,17,48) was shown to influence functional outcome in patients with juvenile-onset AS, became prominent in our group some years after onset. Although we confirmed the predominance of pauciarthritis as reported by others (3)(4)(5)(6)11,(13)(14)(15)(16)(17)(18)(19), its value as a discriminator between juvenile-onset AS and JRA was only marginal at 6 months. Furthermore, the number of patients with juvenile-onset AS extending to polyarthritis at the end of the first year of disease increased steadily thereafter.…”
Section: Burgos-vargas and Vazquez-melladosupporting
confidence: 83%
“…Such symptoms, however, did not occur early in the course of the disease. Fewer than 15% of our patients had pain, stiffness, or reduced mobility of the lumbosacral spine and/or sacroiliac joints in the initial year, and in contrast to some previou:s reports (13)(14)(15)(16)(17)19), none presented with solely axial symptoms. Scarcity of axial disease at onset has been attributed (though this has not been reasonably dlocumented) to the lack of sensitive methods of assessment.…”
Section: Burgos-vargas and Vazquez-melladocontrasting
confidence: 64%
See 3 more Smart Citations